Mondriaan en fotografie : De kunstenaar in beeld. - Coppens, Wietse; Jansen, Leo (Den Haag : Tijdsbeeld Uitgeverij, 2023)
Maris, Sion ; Delbo, Pierre ; Kertész, André ; Lux, Eugene ; Oorthyuyys, Cas ; Holtzman, Harry ; Newman, Arnold ; Landshoff, Hermann ; Glarner, Fritz
boek
Keywords: Mondriaan, Piet